Studies on plant immunity: dissection of the Cf-4/SOBIR1-containing complex in Nicotiana benthamiana - Landeo Villanueva, Sergio Andrés (2023)
Plants have an innate immune system that is organized at two levels: one on the surface of the cells and another in the cytoplasm of the cell. Receptors on the cell surface are involved in the first line of defense, triggering immune responses by perceiving immunogenic patterns that occur during pathogen invasion. The Cf-4 receptor, present on the cell surface of tomato, requires the presence of the co-receptor SOBIR1 to confer resistance to strains of the fungal pathogen Cladosporium fulvum that secrete the Avr4 effector protein. This interaction triggers an immune response that includes a form of programmed cell death known as the hypersensitive response (HR). This thesis explores the early signaling events triggered by the cell surface receptor Cf-4, using the solanaceous model plant Nicotiana benthamiana. Furthermore, a novel method to visualize and quantify HR intensity is presented. Likewise, knowledge of the immune signaling that takes place in Arabidopsis is transferred to plants. Solanaceae, and introduces the use of proximity-dependent labeling, thus revealing the proximal proteome of the Cf-4/SOBIR1 receptor complex in N. benthamiana.